Production of Probiotic Pineapple Juice: Air Extrusion-Spherification System Development and Juice Storage Stability Assessment - Rani, Siti Mariam A.; Lee, Boon-Beng; Elias, Nor Hidawati; Tan, Chung-Ming; Ng, Shi-Yee; Kasim, Khairul Farihan (Jurnal Teknologi dan Industri Pangan, 2025)
Consumption of probiotic beverages has been shown to enhance intestinal health and immune function. Encapsulation technology has been introduced to strengthen the stability of the probiotics in beverages. To improve the stability of the probiotics in pineapple juice, a spherification system was developed to encapsulate Lacticaseibacillus paracasei strain Shirota in Ca-alginate gel microbeads using a co-axial air extrusion method. The effect of process variables (diameter and sphericity of microbeads) in the spherification system was investigated using image analysis software. The interrelationship of the process variables of the system was analyzed using dimensional analysis. Subsequently, the stability of probiotic gel microbeads in pasteurized pineapple juice was assessed. The results showed that the spherification system could produce uniform spherical probiotic gel microbeads with a size range of 0.4–2.6 mm. A mathematical model was developed to enable the production of microbeads with the desired diameter by selecting the proper process variables, specifically the Ohnesorge number, Weber number, and the liquid-to-air mass flow rate ratio. During the refrigerated storage period, the microbeads experienced minor shrinkage and shape distortion, but the pH and total soluble solids of the pineapple juice remained stable. The viability of the encapsulated L. paracasei strain Shirota was well retained in the refrigerated pineapple juice until the ninth day of the storage period. Lastly, the encapsulated L. paracasei strain Shirota demonstrated good tolerance to simulated gastric and intestinal juices. The probiotics spherification system enables the production of probiotic pineapple juice with good stability and viability of the prebiotics.